Victim Protection in Indonesian Criminal Justice: Assessing the Implementation of Restorative Justice as a New Paradigm - Astra Wiguna, I Made Agus; Dana Sugama, I Dewa Gede (Westscience Press, 2025)
The purpose of this study is to analyze the new paradigm in the protection of crime victims in Indonesian criminal law through the implementation of restorative justice, by identifying and comparing the laws of countries that have successfully implemented it, to determine the extent to which the principle has been accommodated in the national legal system. The research method used is normative legal writing with a statutory regulatory approach, legal concept analysis, and comparative law. The results indicate that the paradigm for protecting crime victims in Indonesian criminal law remains dominated by a retributive approach focused on perpetrators, while victims tend to be passive and lack comprehensive recovery. Although regulations such as the Criminal Procedure Code and the Law on Witness and Victim Protection exist, their implementation has not systematically integrated restorative justice principles. This study highlights the need for a new paradigm that places victims as the main subject through a restorative justice approach based on dialogue, recovery, and active participation. Through comparative analysis of practices in New Zealand, Canada, and the Netherlands, it is shown that restorative justice can be effectively implemented if supported by clear regulations, institutional support, and awareness among law enforcement officers. Therefore, the Indonesian criminal law system needs to be updated by formulating a contextual, just, and sustainable restorative justice-based victim protection model, to create a justice system more responsive to victims’ needs.